Cost and value of multidisciplinary fixed-point ocean observatories. (September 2016) - Cristini, Luisa; Lampitt, Richard S.; Cardin, Vanessa; Delory, Eric; Haugan, Peter; O'Neill, Nick; Petihakis, George; Ruhl, Henry A.
Abstract: Sustained ocean observations are crucial to understand both natural processes occurring in the ocean and human influence on the marine ecosystems. The information they provide increases our understanding and is therefore beneficial to the society as a whole because it contributes to a more efficient use and protection of the marine environment, upon which human livelihood depends. In addition the oceans, which occupy 73% of the planet surface and host 93% of the biosphere, play a massive role in controlling the climate. Eulerian or fixed-point observatories are an essential component of the global ocean observing system as they provide several unique features that cannot be found in other systems and are therefore complementary to them. In addition they provide a unique opportunity for multidisciplinary and interdisciplinary work, combining physical, chemical and biological observations on several time scales. The fixed-point open ocean observatory network (FixO3) integrates the 23 European open ocean fixed-point observatories in the Atlantic Ocean and in the Mediterranean Sea. The programme also seeks to improve access to key installations and the knowledge they provide for the wider community, from scientists, to businesses, to civil society. This paper summarises the rationale behind open ocean observatories monitoring the essential ocean variables. It also provides an estimate of the costs to operate a typical fixed-point observatory such as those included in the FixO3 network. Finally an assessment of the type of data and services provided by ocean observations and their value to society is also given. Highlights: Fixed-point observatories are essential to measure Essential Ocean Variables. The annual cost for operating a typical observatory is about 730, 000 Euros. Benefits of investing in sustained ocean observations are higher than the costs. Benefits are economic, environmental and social. Data from integrated networks generates more benefits than fragmented systems.